(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Community health workers are central to India’s strategy for improving maternal healthcare access, particularly among rural, socioeconomically disadvantaged, tribal, migrant, and geographically underserved populations. Accredited Social Health Activists, Anganwadi Workers, Auxiliary Nurse Midwives, and community facilitators contribute to early pregnancy identification, antenatal counselling, birth preparedness, institutional delivery and referral, postnatal follow-up, and family-planning support. However, the extent to which these interventions improve healthcare utilization, continuity of care, maternal morbidity, and maternal mortality requires careful evaluation. Objective: To review the effectiveness of community health worker interventions in improving maternal health outcomes in India, with emphasis on antenatal-care utilization, birth preparedness, institutional delivery, skilled birth attendance, postnatal care, referral of high-risk pregnancies, postpartum contraception, equity, and direct clinical outcomes. Methods: A structured narrative review was conducted using literature identified through PubMed/MEDLINE, Google Scholar, publisher databases, citation tracking, and official repositories of the Government of India and the World Health Organization. English-language publications available through July 2026 were considered. Randomized and non-randomized trials, nationally representative analyses, longitudinal studies, cross-sectional studies, programme evaluations, economic evaluations, qualitative and mixed-methods studies, and relevant systematic reviews were included. Evidence was organized according to intervention type, maternal-care stage, outcome category, and health-system determinant. Because of substantial clinical and methodological heterogeneity, no pooled meta-analysis was undertaken. Results: The most consistent evidence indicates that community health worker exposure increases antenatal-care contact, birth preparedness, institutional delivery, skilled birth attendance, early postnatal contact, and postpartum contraceptive use. National analyses reported higher utilization of facility-based childbirth among women receiving Accredited Social Health Activist services. Coordinated counselling by Accredited Social Health Activists and Anganwadi Workers produced particularly large improvements in birth preparedness and postnatal-care attendance. Participatory women’s groups improved community problem-solving, birth preparedness, and neonatal survival, while digitally supported community health worker programmes increased scheduled home visits and service coverage. Nevertheless, evidence for reductions in severe maternal morbidity or maternal mortality attributable specifically to community health workers remains limited. Screening and referral interventions did not consistently improve composite clinical outcomes when transport, referral completion, or facility readiness were inadequate. Conclusion: Community health worker interventions are effective in improving maternal healthcare utilization and continuity in India. Their greatest demonstrated contribution is as trusted community-based counsellors, mobilizers, navigators, and referral facilitators. Greater effects on severe maternal morbidity and mortality require community interventions to be integrated with reliable transport, responsive referral pathways, respectful maternity care, skilled personnel, blood-transfusion capacity, essential medicines, and high-quality emergency obstetric services.